Response of Fibroblasts from Menkes’ and Wilson’s Copper Metabolism-Related Disorders to Ionizing Radiation: Influence of the Nucleo-Shuttling of the ATM Protein Kinase - Laura El Nachef; Joëlle Al-Choboq; Michel Bourguignon; Nicolas Foray (Biomolecules, 2023)
Menkes’ disease (MD) and Wilson’s disease (WD) are two major copper (Cu) metabolism-related disorders caused by mutations of the ATP7A and ATP7B ATPase gene, respectively. While Cu is involved in DNA strand breaks signaling and repair, the response of cells from both diseases to ionizing radiation, a common DNA strand breaks inducer, has not been investigated yet. To this aim, three MD and two WD skin fibroblasts lines were irradiated at two Gy X-rays and clonogenic cell survival, micronuclei, anti-γH2AX, -pATM, and -MRE11 immunofluorescence assays were applied to evaluate the DNA double-strand breaks (DSB) recognition and repair. MD and WD cells appeared moderately radiosensitive with a delay in the radiation-induced ATM nucleo-shuttling (RIANS) associated with impairments in the DSB recognition. Such delayed RIANS was notably caused in both MD and WD cells by a highly expressed ATP7B protein that forms complexes with ATM monomers in cytoplasm. Interestingly, a Cu pre-treatment of cells may influence the activity of the MRE11 nuclease and modulate the radiobiological phenotype. Lastly, some high-passage MD cells cultured in routine may transform spontaneously becoming immortalized. Altogether, our findings suggest that exposure to ionizing radiation may impact on clinical features of MD and WD, which requires cautiousness when affected patients are submitted to radiodiagnosis and, eventually, radiotherapy.